STRATEGIES FOR THE DEVELOPMENT OF SUPER-PRIORITY TOURISM TO BOOST ECONOMIC GROWTH IN LABUAN BAJO - Reinaldo putra chanai; Cicilia a. Tungga; Olivia L.E. Tomasowa (Universitas Dharmawangsa Medan, 2026)
This research analyzed the development strategies of super priority tourism in increasing economic growth in Labuan Bajo, West Manggarai Regency. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research informants include local government officials, tourism business actors, MSME actors, and local communities around tourist destinations. The data were analyzed using SWOT analysis to identify internal and external factors influencing the development of super priority tourism. The results indicate that Labuan Bajo has significant strengths, such as world-class natural and cultural tourism potential, strong government policy support, and improved tourism infrastructure. Opportunities include increasing domestic and international tourist interest and strong support from central government programs. However, several weaknesses and threats were identified, including limited human resource quality, economic disparities among local communities, and environmental pressures. The appropriate development strategy is to optimize tourism potential through infrastructure enhancement, MSME empowerment, human resource development, tourism promotion digitalization, and the implementation of sustainable tourism principles. The development of super priority tourism in Labuan Bajo has positively contributed to regional economic growth and improved local community welfare.